Structure and Corrosion Performance of a Non-Chromium Process (NCP) Zr/Zn Pretreatment Conversion Coating on Aluminum Alloys. Issue 13 (21st September 2016) - Li, Liangliang; Whitman, Brandon W.; Munson, Catherine A.; Estrada, Rodolfo; Matzdorf, Craig A.; Swain, Greg M.
Abstract : We report on the physicochemical properties and anti-corrosion performance of a non-chromated Zr/Zn conversion coating (NCP) on AA2024-T3. The immersion coating was formed on polished, degreased and deoxidized specimens. Electrochemical methods were used to assess the corrosion inhibition provided by the coating in laboratory tests. The results were compared with environmental exposure tests to assess the stand-alone corrosion protection. Coated AA6061-T6 and 7075-T6 specimens were also used in the environmental tests. Electrochemical testing in naturally-aerated 0.5 M Na2 SO4 + 0.1% NaCl revealed that the NCP coating shifted Ecorr positive by about 250 mV, suppressed anodic more than cathodic current around Ecorr by at least a factor of 10x and shifted Epit more noble. The coating functions more as an anodic inhibitor through barrier layer protection. The coating provided excellent corrosion protection to all three alloys during a 14-day full immersion test in 0.5 M Na2 SO4 + 0.1% NaCl. However during 14-day neutral salt spray and thin-layer mist tests, NCP failed to provide much stand-alone corrosion protection to the aluminum alloys and the anti-corrosion properties were found to be inferior to TCP conversion coatings of comparable thickness. A 7-day beach exposure revealed the NCP coating also provides little resistance to galvanic corrosion on the aluminum alloys as compared to TCP coatings. The results demonstrate that laboratory evaluation of the anti-corrosion properties of non-chromated conversion coatings does not always reflect coating performance during accelerated degradation or environmental exposure. The inferior anti-corrosion behavior of NCP, as compared to TCP, is due to (i) inherent defect density of the former (i.e., reduced throwing power) and (ii) the absence of Cr(III) species.